Women artists at the millennium - Armstrong, Carol M.; Zegher, M. Catherine de (MIT Press, 2006)
"More than thirty years after the birth of the modern women's movement and the beginnings of feminist art-making and art history, the time is ripe to examine the legacies of those revolutions. In Women Artists at the Millennium, artists, art historians, and critics examine the differences that feminist art practice and critical theory have made in late twentieth-century art and the discourses surrounding it. In 1971, when Linda Nochlin published her essay "Why Have There Been No Great Women Artists?" in a special issue of Art News, there were no women's studies, no feminist theory, no such thing as feminist art criticism; there was instead a focus on the mythic figure of the great (male) artist through history. Since then, the "woman artist" has not simply been assimilated into the canon of "greatness" but has expanded art-making into a multiplicity of practices with new parameters and perspectives. In Women Artists at the Millennium artists including Martha Rosler and Yvonne Rainer reflect upon their own varied practices and art historians discuss the innovative work of such figures as Louise Bourgeois, Lygia Clark, Mona Hatoum, and Carrie Mae Weems. And Linda Nochlin considers changes since her landmark essay and looks to the future, writing, "We will need all our wit and courage to make sure that women's voices are heard, their work seen and written about."–Jaquette
OCLC: ocm62766150
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; art féministe; corps; cours; discours dominant; femmes* artistes; har4600; maternité; premier cycle; périodes historiques; représentation; sexisme; systèmes d'oppressions; thématiques

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques